Improvement in Atrial Fibrillation-Related Symptoms After Cardioversion: Role of NYHA Functional Class and Maintenance of Sinus Rhythm - Ferre-Vallverdu M (Dove Medical Press, 2021)
Maria Ferre-Vallverdu,1– 3 Carmen Ligero,1– 3 Rafael Vidal-Perez,4 Antoni Martinez-Rubio,5 Xavier Vinolas,6 Josep M Alegret1– 3 1Department of Cardiology, Hospital Universitari de Sant Joan; 2Institut d’Investigació Sanitària Pere Virgili (IISPV); 3Department of Medicine and Surgery of the University Rovira i Virgili; Reus, Spain; 4Department of Cardiology, Complejo Hospitalario Universitario de A Coruña, A Coruña, Spain; 5Department of Cardiology, Hospital Parc Taulí, Sabadell, Spain; 6Department of Cardiology, Hospital de la Sta, Creu i St Pau, Barcelona, SpainCorrespondence: Josep M AlegretDepartment of Cardiology, Hospital Universitari de Sant Joan. Institut d’Investigació Sanitària Pere Virgili (IISPV). Department of Medicine and Surgery of the University Rovira i Virgili; Reus, Spain. C/Dr Josep Laporte, 4, Reus, 43204, Spain Email josepmaria.alegret@urv.catBackground: The European Heart Rhythm Association (EHRA) score is a proven and validated tool for assessing the symptoms of atrial fibrillation (AF). Little is known about the variables related to this score and how it changes after cardioversion.Methods: We analyzed 744 patients undergoing elective cardioversion in whom AF-related symptoms were assessed at baseline and after 6 months of follow-up using the EHRA score. We assessed the association between the EHRA score and other clinical and echocardiographic variables at baseline and after 6 months of follow-up.Results: At 6 months of follow-up, we observed a reduction in the EHRA score in 50% and worsening in 2.8% of patients who remained in sinus rhythm (SR) compared with 34.6% and 11.3%, respectively, of patients with AF episodes (p< 0.0001). Patients who maintained SR at 6 months were less symptomatic than those with AF (EHRA score 1.13 ± 0.35 vs 1.42 ± 0.59; p< 0.0001). The independent predictors for reduction in the EHRA score after cardioversion were NYHA ≥II at baseline and maintenance of SR (p< 0.0001).Conclusion: The greatest improvement in AF-related symptoms was in patients who remained in SR at 6 months after cardioversion and in patients with worse NYHA functional class at baseline.Keywords: atrial fibrillation, EHRA score, cardioversion, NYHA functional class, sinus rhythm, symptoms improvement